Follow the stars home : a novel - McPhail, Diane C. (John Scognamiglio Books/Kensington Publishing Corp., 2024)
A captivating reimagining of the intrepid woman who-8 months pregnant and with a toddler in tow-braved violent earthquakes and treacherous waters on the first steamboat voyage to conquer the Mississippi River and redefine America. The acclaimed author of The Seamstress of New Orleans brings to life Lydia Latrobe Roosevelt's defiant journey of 1811 in this lush, evocative biographical novel for fans of Paula McLain, Gill Paul, Allison Pataki, and stories about extraordinary yet little-known female adventurers... It's a journey that most deem an insane impossibility. Yet on October 20th, 1811, Lydia Latrobe Roosevelt-daughter of one of the architects of the United States Capitol-fearlessly boards the steamship New Orleans in Pittsburgh. Eight months pregnant and with a toddler in tow, Lydia is fiercely independent despite her youth. She's also accustomed to defying convention. Against her father's wishes, she married his much older business colleague, inventor Nicholas Roosevelt-builder of the New Orleans-and spent her honeymoon on a primitive flatboat. But the stakes for this trip are infinitely higher. If Nicholas's untried steamboat reaches New Orleans, it will serve as a profitable packet ship between that city and Natchez, proving the power of steam as it travels up and down the Mississippi. Success in this venture would revolutionize travel and trade, open the west to expansion, and secure the Roosevelts' future. Lydia had used her own architectural training to design the flatboat's interior, including a bedroom, sitting area, and fireplace. The steamship, however, dwarfs the canoes and flatboats on the river. And no amount of power or comfort could shield its passengers from risk. Lydia believes herself ready for all the dangers ahead-growing unrest among native people, disease or injury, and the turbulent Falls of the Ohio, a sixty-foot drop long believed impassable in such a large boat. But there are other challenges in store, impossible to predict as Lydia boards that fall day. Challenges which-if survived-will haunt and transform her, as surely as the journey will alter the course of a nation...